Sex and Gender Aspects for Patient Stratification in Allergy Prevention and Treatment - De Martinis, Massimo; Sirufo, Maria Maddalena; Suppa, Mariano; Di Silvestre, Daniela; Ginaldi, Lia (International journal of molecular sciences, 2020)
Allergies are rapidly worsening in recent decades, representing the most common immunological diseases. The mechanism of disorders such as asthma, rhinocongiuntivitis, urticaria, atopic dermatitis, food and drug allergies, and anaphylaxis still remain unclear and consequently treatments is mostly still symptomatic and aspecific while developments of new therapies are limited. A growing amount of data in the literature shows us how the prevalence of allergic diseases is different in both sexes and its changes over the course of life. Genes, hormones, environmental and immunological factors affect sex disparities associated with the development and control of allergic diseases, while they more rarely are considered and reported regarding their differences related to social, psychological, cultural, economic, and employment aspects. This review describes the available knowledge on the role of sex and gender in allergies in an attempt to improve the indispensable gender perspective whose potential is still underestimated while it represents a significant turning point in research and the clinic. It will offer insights to stimulate exploration of the many aspects still unknown in this relationship that could ameliorate the preventive, diagnostic, and therapeutic strategies in allergic diseases.